What women value in the midwifery continuity of care model: A systematic review with meta-synthesis. (July 2018) - Perriman, Noelyn; Davis, Deborah Lee; Ferguson, Sally
Highlights: Robust evidence highlights improved clinical outcomes for women accessing continuity of midwifery care. Most women are satisfied with the care they receive, however we know little about the components of this "package" that may contribute to what it is that women value in such a model. This systematic review with meta-synthesis found that the relationship between the childbearing woman and midwife is central and through this additional benefits are realised; trust, personalised care, and empowerment. This has implications for practice and maternity service development. Research evidence highlights the benefits of continuity of care in terms of clinical outcomes, though we know little about the components of this "package" that might contribute to this outcome or what it is that women value in such a model. A systematic review with meta-synthesis is a robust research method that draws together the best available evidence; re-analysing findings to gain a deeper understanding of a phenomenon. The midwife–woman relationship is the vehicle through which personalised care, trust and empowerment are achieved in the continuity of care midwifery model. Abstract: Introduction: There are a number of qualitative studies indicating women are more satisfied with a continuity model of midwifery care however, their experiences have not been understood to gain an overall picture of what it is they value, appreciate and want in such a model. A metasynthesis was undertaken in order to examine the current qualitative literature to gain a deeper understanding of the woman's perspective as a consumer of maternity care in a continuity model. Aim: To identify and synthesise research findings presenting childbearing women's perspectives on continuity of midwifery care. Methods: A search using key words was undertaken using the following databases: CINAHL, Cochrane Library, Ovid, Medline, Nursing Reference Centre and Joanna Briggs Institute. Papers were included if they were published since 2006, in English and included qualitative data from the woman's perspective. The selection process followed was the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Quality appraisal was conducted by all authors using the Critical Appraisal Skills Programme (CASP) tool as a screening tool. This allowed for each paper to be appraised to determine risk of bias. Findings: Thirteen quality appraised papers published between 2006 and 2016 were found which included qualitative data and were related to the woman's experience in a continuity model. Six papers were from Australia, three in the United Kingdom, two in New Zealand and one in the United States of America and Denmark. Themes identified included an overarching concept of the relationship which was underpinned by themes of personalised care, trust and empowerment. Conclusions: The midwife–woman relationship is the vehicle through which personalised care, trust and empowerment are achieved in the continuity of midwifery model of care.